Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and urinary albumin-creatinine ratio (ACR) in US adults: NHANES 2005–2018 - Chaoying Yong; Hongbin He; Chaohui Zhou; Xiaoqin Zhang; Tian Li; Juan Dong; Yingjuan Zhang (PLoS ONE, 2025)
Purpose The ratio of non-high-density lipoprotein cholesterol (NHDL-C) to high-density lipoprotein cholesterol (HDL-C), referred to as NHHR, is an emerging lipid parameter. The relationship between NHHR and the urinary albumin-creatinine ratio (ACR) remains unclear. Therefore, our aim is to explore the potential correlation between NHHR and ACR. Methods Data for this study were sourced from the 2005–2018 National Health and Nutrition Examination Survey (NHANES). Participants under 20 years, pregnant individuals, and those missing NHHR or ACR data were excluded. NHHR, calculated as the difference between total cholesterol (TC) and HDL-C divided by HDL-C, was assessed. Our analysis of the NHHR-ACR association involved multivariable linear regression, smoothed curve fitting, and subgroup analysis. Results A total of 34,734 participants were included, with a mean age of 49.81 ± 17.66 years. The prevalence of albuminuria was 12.66%. Multivariable regression analysis indicated a significant and independent positive association between NHHR and ACR after fully adjustment [β (95% CI): 7.19 (4.54, 9.85), p < 0.0001], particularly among female participants, individuals aged 60 or older, those of Mexican American or Non-Hispanic Black ethnicity, individuals with obesity, hypertension or diabetes. Conclusion Our findings demonstrate a positive correlation between NHHR and elevated ACR in US adults, implying that lowering NHHR may serve as a preventive and palliative strategy for albuminuria.